Comparison of Oral Hygiene Practices between Dental, Medical and Allied Health Sciences Undergraduate Students of Lahore - Anushey Habib, Muhammad Ahmed Hafeez, Nabeela Habib, Maria Noor, Farhan Javed, Omair Anjum (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine how dental education affects the oral hygiene practices in Pakistan. Study design: Descriptive cross-sectional study. Place: FMH College of Medicine and Dentistry, Lahore, Pakistan. Duration: One month. Methodology: A self-administered questionnaire was circulated amongst BDS, MBBS, and AHS students of FMH College of Medicine and Dentistry, Lahore, Pakistan. The responses were analyzed using SPSS version 20.0. Results: Dental students were superior to MBBS and AHS students in brushing frequency, electric toothbrush and water flosser use. Manual toothbrushes are more commonly used than electric toothbrushes in all three groups. More MBBS students believed that electric toothbrushes were better. Flossing proved unpopular. Toothpicks were the preferred interdental aid. Few students use water flossers. Mouthwashes are only used when needed. Most respondents were nonsmokers, but more BDS students smoked. Conclusion: Conclusion: Dental education in Pakistan impacts oral hygiene habits since dental students reported to have superior oral hygiene habits. More MBBS students believed electronic toothbrushes are superior to manual ones, indicating that BDS and AHS students require knowledge of electric toothbrushes. Keywords: Allied Health Sciences, Dental education; Dental students; Medical students; Oral hygiene practices.